1999
DOI: 10.1093/hsw/24.2.103
|View full text |Cite
|
Sign up to set email alerts
|

Managed Care, Meet Community Support: Ten Reasons to Include Direct Support Services in Every Behavioral Health Plan

Abstract: In this article, the performance of community support programs over three decades is assessed through a review of the professional literature, with emphasis on clinical outcomes, cost-effectiveness, and consumer satisfaction. The author argues that for managed behavioral health organizations to serve disabled customers adequately, community support is required. Ten field-tested reasons to include community support services in every behavioral health plan are presented. The author concludes that social workers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…They found treatment for a range of diseases could be managed safely outside an acute hospital. Hughes (1999) assessed the performance of community support programs through a review of the professional literature, with emphasis on clinical outcomes, cost-effectiveness, and consumer satisfaction. He argues that for managed behavioural health organisations to serve disabled customers adequately, community support is required.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They found treatment for a range of diseases could be managed safely outside an acute hospital. Hughes (1999) assessed the performance of community support programs through a review of the professional literature, with emphasis on clinical outcomes, cost-effectiveness, and consumer satisfaction. He argues that for managed behavioural health organisations to serve disabled customers adequately, community support is required.…”
Section: Introductionmentioning
confidence: 99%
“…He argues that for managed behavioural health organisations to serve disabled customers adequately, community support is required. He found that social workers are uniquely qualified to adapt proven interventions from model community support programs to the mission of managed behavioural health organisations, with the potential to remedy problems of access, continuity, and accountability in providing treatment for serious and persistent mental illness (Hughes 1999). Montalto (1997) found some people view hospital in the home (HITH) as encroaching on community health and some routine community nursing is renamed just to maximise income.…”
Section: Introductionmentioning
confidence: 99%
“…As the U.S. population is increasingly covered under managed health and welfare services, the expertise of social work case managers in serving high-risk populations will be sought out by the private managed care sector. Social workers are specifically trained to utilize tested interventions from community-based programming and adapt these to managed care settings in order to deal with problems of access to services, continuity of care, and chronic care management (Hughes, 1999). Despite these opportunities, social workers have generally avoided working for managed care organizations even though their knowledge, skills, and values could greatly benefit persons served by these plans.…”
Section: Introductionmentioning
confidence: 99%
“…among the services for which supply currently does not match the level of need are assertive community treatment, case management, and community-based psychiatric care (butterill et al, 2009). lack of support for people with mental illness has resulted in increased rates of homelessness, incarceration, hospital readmission, and unemployment (Goering, Wasylenki, farkas, lancee, & freeman, 1984;Hughes, 1999;nelson et al, 2009). in contrast, when people have the needed supports, recovery and quality of life are improved (Hughes, 1999).…”
mentioning
confidence: 99%